Appearance of estrogen positive bilateral breast carcinoma with HER2 gene amplification in a patient with aplastic anemia - Čolović, Milica; Todorović, Milena; Čolović, Natasa; Terzic, Tatjana; Karadzic, Katarina; Jurišić, Vladimir (Polish Journal of Pathology, 2014)
Immunosuppressive therapy is one of the standard therapy protocols for aplastic anemia (AA). However, immunosuppressive therapy and androgenic steroids can promote development of solid tumors such as squamous carcinoma, head and neck tumors, adenocarcinoma of the stomach, hepatocarcinoma and breast carcinoma in long surviving patients with aplastic anemia. We present here a rare case of a 56-year-old woman in whom bilateral adenocarcinoma of the breast developed 11 years after the start of immunosuppressive and androgenic steroid therapy for aplastic anemia. Histological examination showed invasive ductal carcinoma with intense nuclear staining for estrogen receptors. Her2 immunohistochemistry was positive for 80% of stained cells, and chromogenic in situ hybridization showed a high level of HER2 gene amplification. This case indicated that a new therapy option is needed for estimation and evaluation to avoid the consequence of cancer occurrence.